Verilog HDL Digital design and modeling - Cavanagh, Joseph (Florida, USA CRC press, 2007)
this eddition provides descriptions of the design module, the test bench module, the outputs obtained from the simulator, and the waveforms obtained from the simulator illustrating the complete functional operation of the design. Where applicable, a detailed review of the topic's theory is presented together with logic design principles, including state diagrams, Karnaugh maps, equations, and the logic diagram
Includes bibliographical references and index
Keywords: Computer industry; Computer programming; Electrical engineering; Programming languages